Adherence to the five moments for hand hygiene among intensive care professionals - Luccas Melo de Souza; Maríndia Fernandes Ramos; Evelin Santos da Silva Becker; Lisiani Celina da Silva Meirelles; Suzana Aparecida Oliveira Monteiro
Objective: to identify the adherence of health professionals of an intensive care unit to the five moments for hand hygiene. Method: cross-sectional analytical study with a quantitative approach, based on secondary data from a database of a hospital infection control service at an institution in southern Brazil. A total of 793 observations were analyzed from July to December 2012. Results: hand washing was not performed in 446 (56.2%) of the observations, and the adherence rate was 43.7%. The greatest adherence to hand hygiene was among the physiotherapists (53.5%) and the lowest adherence was among the nursing staff (29.2%). The indications with the lowest adherence rates to hand hygiene were "before touching the patient" (18.4%) and "before aseptic procedure" (20.9%). Conclusion: we conclude that adherence to hand washing does not comply with the national and international guidelines, especially when we consider the current scenario of growing infections caused by multidrug-resistant microorganisms.